Implementasi Asas-Asas Umum Pemerintahan Yang Baik Dalam Pelayanan Penerbitan E-Ktp: Studi Dugaan Maladministrasi pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Gorontalo - Raihan A. Hanasi; Karmila Djafar; Marcela Puwa; Fadila Al-Hamid; Dwi Rahmatia Nurkamiden (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The issuance of electronic identity cards (e-KTP) represents one of the most fundamental public services administered by the Population and Civil Registration Office (Disdukcapil). Nevertheless, various forms of alleged maladministration in this service delivery continue to be unresolved in many regions, including Gorontalo Regency. This study aims to analyze the implementation of the General Principles of Good Governance (AUPB) in e-KTP issuance practices at Disdukcapil Gorontalo Regency and to identify forms of alleged maladministration. Using a descriptive qualitative approach, primary data were drawn from the 2025 Maladministration Assessment Report of the Ombudsman RI Gorontalo Province Representative and official institutional documents, supplemented by secondary data from scientific journals, legislation, and verified news sources. Findings reveal that Gorontalo Regency obtained a final score of 64.79 with a 'Moderate Quality Without Maladministration' rating the lowest among four evaluated local governments. Three critical areas were identified: (1) non-compliance with service completion time standards, (2) unofficial administrative burdens including out-of-office form purchases, contravening the principle of proportionality, and (3) low public trust levels reflecting accountability deficits. This study contributes by elaborating the legal dimensions of AUPB as a more structured maladministration evaluation framework compared to prior studies focused primarily on public service management dimensions.